Exploring the Impact of Transformational Leadership on Organizational Culture and Employee Performance: The Mediating Role of Job Satisfaction and Motivation In UD. Famili Abadi Pentol Tahunan, Jepara, Central Java - Faqih, Mustofa; Sulistiyono, Eko; Riyoko, Sisno (Raudhah Publisher, 2024)
This study investigates the impact of transformational leadership on organizational culture and employee performance, with a focus on the mediating roles of job satisfaction and motivation. Transformational leadership is recognized for its ability to inspire and motivate employees towards achieving organizational goals through visionary guidance and individualized consideration. The study employs a qualitative literature review methodology to synthesize existing research and theoretical frameworks related to transformational leadership, organizational culture, job satisfaction, motivation, and employee performance. The primary objective of this research is to explore how transformational leadership influences organizational culture and subsequently impacts employee performance. The study examines the mechanisms through which transformational leaders shape organizational culture by promoting values of innovation, collaboration, and employee development. It also investigates how job satisfaction and motivation mediate the relationship between transformational leadership, organizational culture, and employee performance. Findings from the literature review reveal that transformational leadership fosters a positive organizational culture characterized by high levels of trust, empowerment, and engagement among employees. This conducive culture, in turn, enhances job satisfaction and motivation levels, thereby boosting overall employee performance. The mediating effects of job satisfaction and motivation highlight their critical roles in translating leadership behaviors into tangible outcomes at both individual and organizational levels. Implications for practice emphasize the importance of cultivating transformational leadership qualities within organizational leaders to foster a supportive culture that enhances employee performance. Strategies for promoting job satisfaction and motivation are recommended to leverage the full potential of transformational leadership in driving organizational success. Future research directions include exploring contextual factors that influence the effectiveness of transformational leadership across diverse organizational settings and sectors.